Radiological Comparison and Functional Outcomes of Robotic Assisted Medial Unicompartmental Knee Arthroplasty with Metal-Backed Onlay Tibial Components - Haklar, Uğur (Orthop J Sports Med, 2017)
Robotic surgery studies have been increasing considering operative advantages on reducing error and improving functional success in partial knee arthroplasty. We have been curious whether planning and application of knee implants assisted robotically correspond to their radiological outcomes. Moreover, we were also curious about functional outcomes. METHODS: Data were prospectively collected in 42 patients (62 knees) who underwent MAKOplasty, robotic assisted unicondylar medial knee arthroplasty, between June 2013 – December 2015 For evaluation of components’ accuracy, intra-operative robotic analyses were compared with post-operative radiographic alignment. Statistical analysis was done on these values using paired T-Test. Additionally in our clinic with an average follow-up time of 22 months. Clinical outcomes were evaluated with American Knee Society Scoring (AKSS) System. RESULTS: Difference between intra-operative robotic plans and post-operative radiographs was evaluated for the flexion angle of the femoral component, posterior slope of the tibial component and the varus angle of the tibial component. A novel method is used to evaluate the varus angle of the tibial component. All of the errors are <=0.5°, approximately 86% of the errors are <=0.3° while 18% of errors are zero. No significant difference was observed statistically (paired t-test, p<0.05). Post-operatively all 42 patients had excellent knee scores (mean, 99.67) and functional scores (mean, 99.04) on AKSS while pre-operatively 2 were scored fair, 40 were score poor, and functionally 14 were scored fair and 28 were scored poor. CONCLUSION: The difference between robotic plans and radiographic outcomes was statistically not significant where metal-backed onlay tibial components were used.